Antimicrobial activity against CA-MRSA and treatment of uncomplicated nonpurulent cellulitis. Issue 8 (August 2013) - Griffith, Matthew E; Ellis, Michael W
Evaluation of: Pallin DJ, Binder WD, Allen MB et al . Clinical trial: comparative effectiveness of cephalexin plus trimethoprim-sulfamethoxazole versus cephalexin alone for treatment of uncomplicated cellulitis: a randomized controlled trial. Clin. Infect. Dis . 56(12), 1754–1762 (2013). The rise of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) has complicated the empirical antimicrobial treatment of cellulitis. CA-MRSA is frequently the cause of purulent infections, to include purulent cellulitis. The role of CA-MRSA in nonpurulent cellulitis is less clear. Published clinical practice guidelines suggest that CA-MRSA plays only a minor role in nonpurulent cellulitis and that initial treatment should be primarily directed at β-hemolytic streptococci. Until now, there have been no data from prospective randomized control trials to support this recommendation. In this review, we examine the findings from a recent prospective, double-blind, randomized controlled trial that refutes the need for empirical coverage of CA-MRSA when treating nonpurulent cellulitis.